Polymorphic Membrane Protein 17G of Chlamydia psittaci Mediated the Binding and Invasion of Bacteria to Host Cells by Interacting and Activating EGFR of the Host - Li, Xiaohui; Zuo, Zonghui; Wang, Yihui; Hegemann, Johannes H.; He, Cheng (Frontiers in Immunology, 2022)
Chlamydia psittaci (C. psittaci) is an obligate intracellular, gram-negative bacterium, and mainly causes systemic disease in psittacine birds, domestic poultry, and wild fowl. The pathogen is threating to human beings due to closely contacted to employees in poultry industry. The polymorphic membrane proteins (Pmps) enriched in C. psittaci includes six subtypes (A, B/C, D, E/F, G/I and H). Compared to that of the 1 pmpG gene in Chlamydia trachomatis (C. trachomatis), the diverse pmpG gene-coding proteins of C. psittaci remain elusive. In the present study, polymorphic membrane protein 17G (Pmp17G) of C. psittaci mediated adhesion to different host cells. More importantly, ectopic expression of Pmp17G in C. trachomatis upregulated infections to host cells. Afterwards, crosstalk between Pmp17G and EGFR was screened and identified by MALDI-MS and Co-IP. Subsequently, EGFR overexpression in CHO-K1 cells and EGFR knockout in HeLa 229 cells were assessed to determine whether Pmp17G directly correlated with EGFR during Chlamydial adhesion. Finally, the phosphorylated activated form of EGFR was recognized by Grb2, triggering chlamydial invasion. Based on above evidence, Pmp17G possesses adhesive property that serve as an adhesin and activate intracellular bacterial internalization by recognizing EGFR during C. psittaci infection